English Language Education Students’ Perceptions On The Use Of AI Technology As An Academic Tool At Tadulako University - Arfiyah Eka Putri; Hasna Hasna; Abraham Abraham; Mochtar Marhum (Hasanuddin University, 2026)
This research examines the perceptions of English Language Education students at Tadulako University regarding the use of Artificial Intelligence (AI) as an academic support tool. The study employed a qualitative descriptive design. Data were collected through questionnaires and semi-structured interviews involving active students in the 2024/2025 academic year. The findings indicate that most students have positive perceptions of AI in academic learning. Students perceive AI as useful for generating ideas, improving writing accuracy, supporting personalized learning, and providing real-time feedback. These features help students complete academic tasks more efficiently and increase their learning motivation. This finding suggests that AI can support students in overcoming common academic difficulties, particularly in writing and independent learning. The results are consistent with the Technology Acceptance Model (TAM), which emphasizes perceived usefulness and perceived ease of use as key factors influencing technology acceptance. In this study, students accepted AI mainly because it is easy to use and provides immediate benefits in their academic activities. When students find a technology helpful and simple, they are more likely to integrate it into their learning process. However, the study also reveals several concerns. Some students expressed worries about over-dependence on AI, inaccurate information, and ethical issues such as plagiarism and loss of originality. These concerns indicate that while AI offers many advantages, its use also presents potential risks if not properly guided. Despite these challenges, most students demonstrated a good level of ethical awareness. They emphasized that AI should be used as a supporting tool rather than a replacement for their own thinking and academic effort. This shows that students understand the importance of maintaining academic integrity while using AI.